THE ABORTION‘S ACT AMONG BLACK AMERICAN IN THE UNITEDSTATES (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2012)
This research focuses on the act of abortion among Black People in the United States based on history, the society environment, and two big major issues regarding the abortion act such as Roe vs Wade, and Pro Choice - Pro Life. Black people become the central point on this research because the fact shows that the largest population which do the abortion act and mostly considered as Black American in the first plce and the second one is from Hispanic American rather than any other minority groups or even the White American itself and this happened based on the history of racial discrimination or segregation toward BlackPeople. This research uses library research in term of qualitative method, and applying descriptive method in analyzing the data. The approaches which are used in this research are the approaches which have a great related with the society and social problem. This approaches well known with the term of interdispliner study which have main purpose to elaborate many perspectives to become primarysources. The different treatment toward Black People based on racial discrimination experienced becomes the trigger why do Black People placed the highest number in doing abortion act in the UnitedStates.